Families Matter: Social Support and Mental Health Trajectories Among Lesbian, Gay, Bisexual, and Transgender Youth - McConnell, Elizabeth A.; Birkett, Michelle; Mustanski, Brian (Journal of adolescent health, 2016)
Lesbian, gay, bisexual, and transgender (LGBT) adolescents are at greater risk for mental health problems than their heterosexual peers, in part due to victimization. Social support, particularly from families, has been identified as an important promotive factor. However, little is known about how LGBT youth experience multiple forms of support or how early support predicts mental health across adolescence and into young adulthood. In an analytic sample of 232 LGBT youth aged 16–20 years at baseline across 5.5 years, we compared developmental trajectories of psychological distress between three empirically derived social support cluster types at baseline: those who reported uniformly low support, those who reported uniformly high support, and those who reported nonfamily support (i.e., high peer and significant other but low family support). Longitudinal multilevel modeling, controlling for age, victimization, and social support at each wave, indicated key differences between cluster types. Youth in the low and nonfamily support clusters reported greater distress across all time points relative to youth in the high support cluster; however, they also showed a sharper decline in distress. Youth in the nonfamily cluster gained family support across adolescence, such that they resembled youth in the high support cluster by early adulthood. Findings underscore the importance of family support for LGBT youth. Youth who lack family support, but who have other forms of support, report a decrease in psychological distress and an increase in family support across adolescence. Youth who are low in all forms of support continue to exhibit high distress.